Unleash the Math Magician in You - Kamal, Anita (Educational Trend (A Journal of RIE, Ajmer - NCERT), 2025)
Math is one of those subjects that is very crucial to learn. Its concepts are applied in almost every area of life – many problems can frequently be solved through the application of math concepts; thus it is commanding to learn and understand how to solve math problems. Moreover, math problem-solving skills and strategies can help to foster accuracy and inspire confidence. The state of a student‘s math development as they begin school determines what they must learn and how to achieve mathematical proficiency.